C-Reactive Protein and Cancer: Interpreting the Differential Bioactivities of Its Pentameric and Monomeric, Modified Isoforms - Potempa, Lawrence A.; Rajab, Ibraheem M.; Olson, Margaret E.; Hart, Peter C. (Frontiers in Immunology, 2021)
C-reactive protein (CRP) was first recognized in the 1940s as a protein that appeared in blood during acute episodes of infectious disease. Its presence and pharmacodynamics were found in essentially all diseases that involved tissue damage and inflammation. Identified as a major component of the innate, unlearned immunity, it became a useful diagnostic marker for the extent of inflammation during disease exacerbation or remission. Efforts to define its true biological role has eluded clear definition for over a half-century. Herein, a unifying concept is presented that explains both pro-inflammatory and anti-inflammatory activities of CRP. This concept involves the recognition and understanding that CRP can be induced to undergo a pronounced, non-proteolytic reorganization of its higher-level protein structures into conformationally distinct isomers with distinctive functional activities. This process occurs when the non-covalently associated globular subunits of the pentameric isoform (“pCRP”) are induced to dissociate into a monomeric isoform (“mCRP”). mCRP consistently and potently provides pro-inflammatory activation and amplification activities. pCRP provides weak anti-inflammatory activities consistent with low-level chronic inflammation. mCRP can spontaneously form in purified pCRP reagents in ways that are not immediately recognized during purification and certification analyses. By now understanding the factors that influence pCRP dissociate into mCRP, many published reports investigating CRP as a biological response modifier of host defense can be reevaluated to include a discussion of how each CRP isoform may have affected the generated results. Specific attention is given to in vitro and in vivo studies of CRP as an anti-cancer agent.